Masuknya Peradaban Islam ke Indonesia dan Peran Walisongo dalam Proses Islamisasi Nusantara - Shelfiya Anjani (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2024)
Broadly speaking, there are three theories about the arrival of Islam to Indonesia, namely the Gujarat theory, the Arabic theory and the Persian theory. The arrival of Islam to various regions in Indonesia did not occur simultaneously. Likewise, the various regions and kingdoms he visited had opposing socio-cultural and political conditions. Historians agree that Sumatra was the region where Islam first visited. The word wali songo is a combination of "wali" and "songo". The word wali is a form of the word waliyullah and comes from Arabic which means someone who loves and is loved by Allah. Then songo comes from Javanese which means nine. With this, wali songo is interpreted as wali nine, namely nine people who love and are loved by Allah SWT. Wali Songo has had a big influence in various fields in the process of spreading Islamic teachings in Indonesia, especially in Java. These fields include education, politics and da'wah.